1998
DOI: 10.1161/01.cir.98.16.1688
|View full text |Cite
|
Sign up to set email alerts
|

Quantification of Effects of Global Ischemia on Dynamics of Ventricular Fibrillation in Isolated Rabbit Heart

Abstract: Background-Ventricular fibrillation (VF) leads to global ischemia of the heart. After 1 to 2 minutes of onset, the VF rate decreases and appears more organized. The objectives of this study were to determine the effects of no-flow global ischemia on nonlinear wave dynamics and establish the mechanism of ischemia-induced slowing of the VF rate. Methods and Results-Activation patterns of VF in the Langendorff-perfused rabbit heart were studied with the use of 2 protocols: (1) 15 minutes of no-flow global ischemi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

12
93
1
1

Year Published

1999
1999
2009
2009

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 97 publications
(107 citation statements)
references
References 26 publications
12
93
1
1
Order By: Relevance
“…Extracellular K ϩ accumulation is a prominent factor of myocardial ischemia (7). Reduced excitability resulting from hyperkalemia increases spatiotemporal periodicity and stabilizes sources of VF in isolated heart preparations (23,25,43). These effects have been explained in terms of the increase in the core size of the spiral wave (25) or flattening APDR (23).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Extracellular K ϩ accumulation is a prominent factor of myocardial ischemia (7). Reduced excitability resulting from hyperkalemia increases spatiotemporal periodicity and stabilizes sources of VF in isolated heart preparations (23,25,43). These effects have been explained in terms of the increase in the core size of the spiral wave (25) or flattening APDR (23).…”
Section: Discussionmentioning
confidence: 99%
“…Yet, the effects of ischemia on VF dynamics are complex and poorly understood. Reduced excitability resulting from hyperkalemia increases spatiotemporal periodicity and stabilizes sources of VF in isolated heart preparations perfused with physiological solutions (23,25,43). However, in the open-chest dog, Huang et al (19) have recently found a biphasic type of evolution of activation patterns during VF, with a transient phase of increased spatiotemporal organization between 1 and 1.5 min after VF onset followed by a decrease in the organization in later phases of VF.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…To aid in the development of new approaches to defibrillation, 20,22 it would be invaluable to make available electrophysiological mapping data collected during VF in model systems. A more informed analysis of VF will lead to a deeper understanding of the mechanism of complex wave phenomena, which underlie not only sudden cardiac death 23,24 but possibly other pathophysiological dynamics, such as seizure disorders.…”
Section: Potential Benefitsmentioning
confidence: 99%
“…Therefore, we believe that the termination occurred because of the presence of a single rotor that maintained AF. Mandapati et al 13 reported that the size of the core of a stationary spiral wave in an isolated rabbit ventricle was significantly increased by the addition of small concentrations of sodium channel blocker. They suggested that a reduction of sodium current enlarges the core size and prolongs the rotation period, which is consistent with these findings.…”
Section: Effects Of Pilsicainide On Electrophysiological Action Durinmentioning
confidence: 99%